A Study on Comparative Performances of Hybrid and Convential Rice Varieties in Aman Season - Awal, MA; Habib, AKMA; Hossain, MA (Journal of Agriculture & Rural Development, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> An experiment was done at farmer's field in Sherpur district to evaluate the comparative performance of two hybrid rice varieties, Sonarbangla-2 and Sonarbangla-3 with three conventional modern commercial varieties BRRIdhan32, BRRIdhan33 and BR11 in Transplanted aman season of 2003. It is revealed that the hybrids and conventional rice varieties differed significantly among themselves with respect to different parameters under study. The highest grain yield (6.20t/ha) was recorded from the hybrid Sonarbangla-3 followed BRRIdhan-32 (5.70 t/ha) and the lowest in BRRIdhan-33 (4.17t/ha) and these differences were statistically significant. However, BRRIdhan-32 obtained significantly higher yield compared to the hybrid Sonarbangla-2. Further, it produced the maximum amount of straw (8.6 t/ha), which varied significantly with all others. Minimum days to 1st flowering (92) and maturity (108) were noticed in Sonarbangla-2 followed by Sonarbangla-3 (95 and 115), respectively. Both the hybrid had heavier grain weight (28.33-31.00g) than those of the conventional varieties (22-25g). It is noted that the hybrids maintained distinct statistical edge over the conventional varieties with regard to most of the parameters. Thus, the hybrid Sonarbangla-3 was found superior to conventional varieties for transplanting in the aman season in Bangladesh. Key words: Sonarbangla-2, Sonarbangla-3, conventional varieties, cropping pattern. DOI = 10.3329/jard.v5i1.1451 J Agric Rural Dev 5(1&2), 13-16, June 2007